The short-term disadvantageous of tension-suture and spica cast application in exstrophy-epispadias complex reconstruction: a case report - Ida Bagus Putra Pramana; Anak Agung Gde Oka; Gede Wirya Kusuma Duarsa; Kadek Budi Santosa; I Wayan Yudiana; Pande Made Wisnu Tirtayasa (DiscoverSys Inc., 2019)
Background: Exstrophy-epispadias complex (EEC) represents a spectrum of genitourinary malformations and associated with another congenital anomaly. EEC is a rare congenital disability. EEC affects the genitourinary system, anterior abdominal wall, musculoskeletal system, spine and anus. The surgical outcome has a lot of potential complications in patient with EEC. The decision to first approach is important for the next step. Herein, we reported a case of EEC with several anomalies. Case Description: A new-born male was born with section cesarean at 38 weeks of gestation from 34-year-old mother, and this is from the second pregnancy. The weight was 3300 grams, and the height was 48 centimetres. There was an abdominal wall defect with an exposed evaginated bladder plate with urine draining from the defect. A complete dorsally opened urethral plate was seen from the bladder neck down to the glandular grove. The patient was diagnosed with Exstrophy-epispadias complex (EEC). A 2 stage repair was conducted in this patient. After 10 days post-operation, the wound became dehiscence and got sepsis postoperatively as well as lead to die in the day 20.Conclusion: Wound dehiscence following reconstruction is very critical inpatient with EEC. Tension suture and spica cast application can be disadvantageous inpatient with EEC.